The assessment of ambient air pollution trend in Klang valley, Malaysia - A. Rahman, Siti Rahmah; Syed Ismail, Sharifah Norkhadijah; Ramli, Mohammad Firuz; Latif, Mohd Talib; Zainal Abidin, Emilia; Praveena, Sarva Mangala (Scientific & Academic Publishing, 2015)
This study aims to explore the trend of ambient air pollution (i.e. PM10, CO, NO2, O3) within the eight selected Malaysian air monitoring stations in Klang valley of five years database (from 2007 to 2011). It integrated statistical analysis to compare the air pollution database with the recommended Malaysian Ambient Air Quality Guidelines (MAAQG) standard and to determine the association between pollutants and meteorological factors. The geographical information system (GIS) softwarewas used to assess the spatial trend of air pollutants across the north-east and south-west monsoons and the Principal Component Analysis (PCA) to determine the major sources of the air pollution. The statistical analysis showed the hourly trends (1-hour averaging time) of PM10, CO, O3 and NO2 in the Klang Valley were below the MAAQG standard. Klang recorded the highest concentration of PM10, while Petaling Jaya recorded the highest concentrations of CO and NO2 and Shah Alam recorded the highest O3. The 24-hour data for PM10 was found to exceed the MAAQG throughout the five-year period. All pollutants were positively correlated with each other with the exception of CO and O3. Meteorological factors, i.e. ambient temperature, wind speed and humidity were alsosignificantly associated with the pollutants. The spatial distribution map indicated that the PM10 levels remain highly concentrated during the south-west monsoon (hot and dry season), while the CO levels were highly concentrated during the north-east monsoon (wet season). NO2 and O3 were highly determined during the first inter-monsoon.